Development of Village Digitization through the “Kaline X Mbangun Desa(in)” in Srihardono Village Bantul Yogyakarta - Damar, Dendy Dio; Kinasih , Audrey Vania Zahrani; Khasanah, Rizka Aprilia Nur; Wicaksono , Sandra Ramadhani; Junaedi , Fajar (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
The village information system implementation should continue to be optimized by every village in Indonesia. However, to make it happen, it is necessary to develop the village information system in every village, one of which is the Online Kalurahan Program (Kaline). The method used is by digitizing and branding the Kalurahan located in Srihardono Village Bantul Yogyakarta. This program can be realized in approximately two months by conducting research and focus group discussion with Srihardono Village staff and local community representatives. Then, we conducted digital content production. The results of this service are the creation of village design assets, profile books, website homepages, social media templates, and village profile videos.